Exact Foldy-Wouthuysen transformation for real spin-0 particle in curved space - Accioly, A. [UNESP]; Blas, H. [UNESP] (American Physical Society (APS), 2002)
Up to now, the only known exact Foldy-Wouthuysen transformation (FWT) in curved space is that concerning Dirac particles coupled to static spacetime metrics. Here we construct the exact FWT related to a real spin-0 particle for the aforementioned spacetimes. This exact transformation exists independently of the value of the coupling between the scalar field and gravity. Moreover, the gravitational Darwin term written for the conformal coupling is one-third of the corresponding term in the fermionic case. There are some arguments in the literature that seem to favor the choice (Formula presented) We rehearse a number of claims of these works. © 2002 The American Physical Society.